The Role of Human Resource Management Practices in Strategic Success: An Analytical Study of the Opinions of Administrative Leaders in a Sample of Private Universities in Erbil - إبراهيم ولي, احلام; كريم خان يحيى, سمية (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
The research aims to determine the relationship and impact of human resource management practices in private universities, represented by its dimensions (human resource planning, polarization, selection, performance evaluation, human resource maintenance), in the dimensions of strategic success represented by (adaptation, growth, survival). The general framework of the research is the research problem, which was identified by raising several questions about the nature of the relationship and the effect between the independent variable (human resource management practices) and the dependent variable (strategic success). All of them were subjected to multiple tests, and the questionnaire was used as the main tool for obtaining data. The research followed the descriptive analytical approach, as the main and sub-variables were described, as well as the analysis of relationships and influence between the variables, the research population represent all the head of departments in all the private universities in the city of Erbil, the Kurdistan Region of Iraq, which numbered (9) universities. The sample was represented by (5) universities, and the respondents were (76) heads of scientific departments in the universities selected from. The hypotheses were tested through a set of statistical tests using the computer program (SPSS V.23). The research reached a set of conclusions, the most important of which is the existence of positive correlations and strong influences between the main and sub-variables, at the macro and micro levels. The research suggested a set of proposals, including the necessity of harnessing the strong relations between the two variables and directing them towards serving the researched universities.